We Do Not Know the Population of Every Country in the World for the past Two Thousand Years - Timothy Guinnane (Center for Economic Studies and ifo Institute (CESifo), 2021)
Economists have reported econometric results that rely on estimates of the population of every country in the world for the past two thousand or more years. The underlying source is usually McEvedy and Jones' Atlas of World Population History, published in 1978. The McEvedy and Jones data have important weaknesses. The reported populations for years before 1500 are, for most countries, little more than guesses, as are many estimates for more recent times. Research relying on McEvedy and Jones cannot take advantage of improved estimates reported since 1978. McEvedy and Jones often infer population sizes from their view of a particular economy, making their estimates poor proxies for economic growth. Although some economists treat the African data as pertaining to modern nation-states, in most cases it is not. With a few welcome exceptions, economists using this source do not take the measurement error issues seriously. Results that rest on McEvedy and Jones are unreliable. The willingness to rely on such data discourages effort to provide serious improvements.
Keywords: N00; N10; O40; O47; J10; C18; 330; long-run growth; historical populations; measurement error; McEvedy and Jones